Analysis of reported cases of sexual violence in Espírito Santo, southeastern Brazil, 2011-2018 - Franciéle Marabotti Costa Leite; Beatriz Ferrari; Karina Fardin Fiorotti; Márcia Regina de Oliveira Pedroso; Bruna Venturin; Nicole Letourneau; Fábio Lúcio Tavares (BMC, 2023)
Abstract Background sexual violence includes all sexual acts consummated or attempt to obtain them, unwanted sexual comments and actions that go against the other's sexuality through coercion, which can be done through the use of physical force, psychological pressure, extortion or threat, this phenomenon appears in all life cycles. Identified the frequency and characteristics of sexual violence against women in a state in the southeastern region of Brazil. from 2011 to 2018. Method this is a cross-sectional epidemiological study that evaluated all cases of sexual violence reported in Espírito Santo, present in the Information System of Diseases and Notifications of the Ministry of Health from 2011 to 2018. The analysis was based on performed in Stata 14.1. Results the prevalence of notification of sexual violence was 13.2% (CI95%: 12.8-13.5). Most victims were women (PR: 3.38), aged between 0 and 9 years (PR: 19), with a higher prevalence in people without disabilities or disorders (PR: 1.18) and residents of urban/periurban area (PR: 1.15). Men were the most frequent aggressors (PR: 13.79), with the most prevalent cases being reported by people unknown to the victim (PR: 6.01). The occurrence was 78% more reported at home and committed by an aggressor (PR:1.19). Most cases were repeated (PR:1.13). Conclusions the notification of sexual violence in Espírito Santo was high and evidenced the vulnerability of some groups, as well as the profile of the perpetrators. It is necessary to work on training professionals in the areas of health and education in relation to the identification of cases of sexual violence, mainly due to the significant involvement of children and adolescents.